Dakryolitiáza--rozbor 15 prípadů - Komínek, P; Cervenka, S; Doskárová, S; Heiderová, D; Slabík, D; Husek, P; Buryska, J (Ceska a slovenska oftalmologie, 2002)
Dacryoliths are found in 15-20% patients subject to dacryocystorhinostomy. Dacryoliths are formed by proteins or calcium and phosphate salts. In the development or dacryolithiasis participates chronic inflammation of the sac, it is found more frequently in women where some part is played by the structure of the lacrimal duct, hormonal influence and the use of cosmetic preparations. A typical sign of the disease in the variability of complaints and results of clinical examinations. Assessment of the diagnosis before surgery can be facilitated by dacryocystography. The method of choice in dacryolithiasis is dacryocystorhinostomy. The authors present their own group of 16 dacryolithis which they observed 10x in women and 5x men. The concrements were examined by the method of infrared spectroscopy and gas chromatography. All were formed by proteins; calcium and phosphate salts were not found In all patients after dacryocystorhinostomy the complaints disappeared.
Keywords: senioři; senioři nad 80 let; Calculi; kojenec; mladiství; Middle Aged; mužské pohlaví; Infant; Adult; kaménky; dítě; Child; Aged, 80 and over; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; lidé středního věku; nemoci slzného ústrojí; dospělí; Female; Aged; Lacrimal Apparatus Diseases; Adolescent; lidé; Male